Luteolin and 4-Hydroxybenzoic Acid from the Leaves of Vitex negundo L. - W.C, Ling,; F, Ahmad; Ali R, Mat (Malaysian Journal of Science, 2005)
Chemical investigation on the leaves of medicinal plant Vitex negundo or laggundi had been carried out. The sample of this species was extracted with petroleum ether, chloroform, ethyl acetate and ethanol consecutively with a soxhlet apparatus. The individual crude extract was fractionated with vacuum liquid chromatography and further purified by column chromatography. The crude ethyl acetate extract yielded two pure compounds, which were characterized as 4-hydroxybenzoic acid and luteolin. The structures of the pure compounds were elucidated using various spectroscopic techniques such as NMR, FTIR, UV-VIS and GC-MS.